Photoluminescence effect on phosphorous irradiated zinc oxide (ZnO) nanotetrapods synthesized by simple thermal oxidation method - Bushra Aziz; Abdul Majid; lubna ghani; Iffat Aziz (Journal of Physics and Its Applications, 2020)
The irradiation effect on ZnO tetrapods was studied by Pelletron Tandem Accelerator at room temperature. ZnO tetrapods were synthesized by a simple thermal oxidation method by the vapors solid mechanism. The tetrapods were irradiated by phosphorous ion beam at different doses (1x1014, 5x1014, 1x1015, 2.5x1015, and 5x1015 ions/cm2) having irradiation energy of 1MeV. After irradiation, these samples were characterized by scanning electron microscope (SEM), photoluminescence (PL), and energy dispersive spectrum (EDS). Photoluminescence (PL) spectra of our samples show that near band emission and deep level emission peaks increases with increasing dose and these emission peaks are defects related peaks. The PL spectra showed that the emission at 3.31eV and 3.26 eV attributed to a conduction band of phosphorus-related acceptor transition and a donor to the acceptor pair transition, respectively.